Temperature-programmed capillary high-performance liquid chromatography with atmospheric pressure chemical ionization mass spectrometry for analysis of fatty acid methyl esters - Vrkoslav, Vladimír; Rumlová, Barbora; Strmeň, Timotej; Cvačka, Josef (Journal of separation science, 2020)
A new capillary high-performance liquid chromatography method with atmospheric pressure chemical ionization mass spectrometry was developed for the analysis of fatty acid methyl esters and long-chain alcohols. The chromatographic separation was achieved using a Zorbax SB-C18 HPLC column (0.3 × 150 mm, 3.5 μm) with a mobile phase composed of acetonitrile and formic acid and delivered isocratically at a flow rate of 10 μL/min. The column temperature was programmed simply, using a common column oven. Good reproducibility of the temperature profile and retention times were achieved. The temperature programming during the isocratic high-performance liquid chromatography run had a similar effect as a solvent gradient; it reduced retention times of later eluting analytes and improved their detection limits. Two atmospheric pressure chemical ionization sources of the mass spectrometry detector were compared: an enclosed conventional ion source and an in-house made ion source with a glass microchip nebulizer. The enclosed source provided better detectability of saturated fatty acid methyl esters and made it possible to determine the double bond positions using acetonitrile-related adducts, while the open chip-based source provided better analytical figures of merit for unsaturated fatty acid methyl esters. Temperature-programmed capillary high-performance liquid chromatography is a promising method for analyzing neutral lipids in lipidomics and other applications.
Keywords: lipids; high-performance liquid chromatography; double bonds; lipidomics; temperature programming